CULTURAL ASPECTS OF VERBAL COMMUNICATION AT THE MEMINANG CEREMONY IN SOLOK DISTRICT (COMMUNICATION ETHNOGRAPHY) - Marta, Redo Andi; Rahayu, Zona Rida (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
Research on meminang ceremonies is motivated by communication between speakers and interlocutors. Thus situation contains cultural aspects in verbal communication. This research aims to explain the cultural aspects pf verbal communication at the meminang ceremony in Solok Regency (Ethnography of Communication). To achieve the objectives of this research, researchers used a qualitative approach with ethnography communication methods. Research data collection uses observation, interviews, field notes and documentation (photos) methods. The analysis of this research data is, (1) transcribing the listening and recording results, (2) translating Minangkabau language into Indonesian, (3) recording quotations according to the topics discussed, (4) coding each research data, (5) classifying quotations in the cultural aspect of verbal communication, (6) conducting analysis and discussion and (7) formulating conclusions and suggestions. The results of the research show that the negotiations carried aut by speakers and interlocutors in the meminang ceremony are viewed from the cultural aspects of communication in the form of verbal communication, including the culture in verbal communication in this research in the form of connotations and the use of greetings.